O SISTEMA CARCERÁRIO FEMININO: ANÁLISE PELO VIÉS CRIMINOLÓGICO E PELA INTERSECCIONALIDADE RACIAL, ECONÔMICA E SOCIAL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This research examines female incarceration in Brazil, focusing on black and brown women in socio-economic vulnerability. The criminological analysis addresses dynamics of exclusion that lead to female criminality, often related to drug trafficking. The study revisits historical approaches and stereotypes that marginalize these women, proposing an intersectional analysis to assess the causes and consequences of this phenomenon. Based on an analysis of the existing literature on the subject, the aim was to identify the chain of events in the life of an incarcerated woman, in order to understand the factors that facilitate her insertion in the Brazilian prison system, including relevant points such as racial, economic and social intersectionality. To this end, a contextualization of the life of a woman before, during and after imprisonment was carried out, with a focus on obtaining an analysis of the trajectory that led her to criminality, and the reason for the high rate of recidivism. In addition to the bibliographical analysis, the dialectical deductive method was adopted to move towards conclusive hypotheses, launched through an aspect of the adopted methodology, aware of the inexhaustible reasons that motivate this social reality.